DEVELOPMENT OF INTERACTIVE DISCOVERY LEARNING MODULE ASSISTED BY VIR-LAB TO IMPROVE UNDERSTANDING OF PHYSICS CONCEPTS - Susannti, Anggraeni Dwi (UIN Sunan Gunung Djati Bandung, 2025)
The aim of this research is to develop a discovery learning e-module assisted by vir-lab to increase understanding of physics concepts in the matter of vibrations, waves and light, and to test the feasibility of a discovery learning e-module assisted by vir-lab to increase understanding of physics concepts. The method used in this research is research and development using a 4D development model consisting of define, design, develop and disseminate stages. The data collection method in this research is by analyzing student response questionnaires regarding the use of e-modules in learning and giving tests before (pretests) and after (posttest) in using e-modules to determine students' understanding of physics concepts. Based on the validation results, the experts got valid results, based on the results of students' responses in using the e-module, they got an average percentage of 81%, including the